The Role of Financial Literacy in Mediating the Effect of Kaizen Concept Implementation on Production Cost Control among Food and Beverage MSMEs in Pangkajenne City - Salida , Amrizal; Fadlina, Fadlina; Kurniawan, Kurniawan; Haeril, Haeril; Suriadi, Suriadi (Amkop Management Accounting Review (AMAR), 2024)
This study aims to examine the effect of Kaizen concept implementation on production cost control among micro, small, and medium-sized enterprises (MSMEs) in the food and beverage sector in Pangkajenne City, and to investigate the mediating role of financial literacy. One of the persistent issues faced by MSMEs is weak cost control due to inadequate cost recording and management practices. The Kaizen approach, which emphasizes continuous and incremental improvement, is expected to enhance cost efficiency. However, its effectiveness is believed to be maximized when supported by sufficient financial literacy. A descriptive quantitative method was employed, and data were analyzed using Partial Least Squares (PLS). Data were collected through questionnaires distributed to 97 food and beverage MSME owners operating container-based outlets in Pangkajenne. The results reveal that: (1) Kaizen implementation has a positive and significant effect on production cost control; (2) financial literacy also has a positive and significant effect on production cost control; and (3) financial literacy significantly mediates the relationship between Kaizen implementation and production cost control. These findings suggest that achieving optimal cost efficiency requires not only consistent application of Kaizen practices but also strengthening financial literacy among MSME actors.